ELEVATED ONE-HOUR POSTLOAD PLASMA GLUCOSE LEVELS IDENTIFY CORONARY HEART DISEASE PATIENTS WITH GREATER SEVERITY OF CORONARY ARTERY LESIONS AND HIGHER RISK OF ONE-YEAR RE-ADMISSION. (April 2021) - Cao, Lifei; Wang, Ping; Luan, Hui; Chen, Hui; Luo, Chaodi; Tian, Gang
Abstract : Objective: To investigate the relationship of one-hour postload plasma glucose (1-h PG) during the oral glucose tolerance test (OGTT) with the severity of coronary artery lesions and risk of one-year re-admission with adverse cardiovascular events in coronary heart disease (CHD) patients with normal glucose tolerance (NGT). Design and method: 266 consecutive CHD patients who underwent coronary angiography and had NGT confirmed by OGTT during hospitalization were prospectively enrolled and followed in two groups according to the 1-h PG cut-off point of 155 mg/dL (1-h PG<155 mg/dL, n = 149 and elevated 1-h PG levels, n = 117). Angiographic severity was assessed by number of diseased vessels, lesion morphology and Gensini score. The risk of one-year re-admission with adverse cardiovascular events after discharge was analysed using Kaplan-Meier analysis. Results: Subjects with elevated 1-h PG levels had higher incidence of multi-vessel disease and complex lesions (76.9% vs 47.7%, P < 0.001 and 48.7% vs 32.2%, P = 0.002), Gensini score [60(33–88) vs 28(16–44), P < 0.001], and risk of one-year re-admission (19.8 vs 8.9%, Breslow test P = 0.016) than subjects with a 1-h PG<155 mg/dL. In the stepwise multivariate regression analysis, the variable that remained significantly associated with the Gensini score was 1-h PG accounting for 13.1% of its variation. Subgroup analyses by sex showed that men with elevated 1-h PG levels had higher incidence of complex lesions (46.8% vs 32.1%, P = 0.033) and risk of one-year re-admission (19.9 vs 8.9%, Breslow test P = 0.031) than men with a 1-h PG<155 mg/dL, but this trend was not seen in women. Figure. No caption available. Figure 1. Kaplan–Meier curves showing the cumulative risk of one-year re-admission with adverse cardiovascular events after discharge in all subjects and stratified by sex. Conclusions: CHD patients with NGT and elevated 1-h PG levels had a greater severity of coronary artery lesions and an increased risk of re-admission with adverse cardiovascular events, particularly in men.